1986
DOI: 10.1007/bf00377106
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of tiger swallowtail subspecies to secondary metabolites from tulip tree and quaking aspen

Abstract: Two subspecies of the eastern tiger swallowtail butterfly, Papilio glaucus, exhibit reciprocal inabilities to survive and grow on each other's preferred foodplant. P. g. canadensis R. & J. performs well on quaking aspen (Populus tremuloides Michx.) but not on tulip tree (Liriodendron tulipifera L.); P. g. glaucus L. performs well on tulip tree but not on quaking aspen. This study was designed to test the hypothesis that secondary metabolites in tulip tree and quaking aspen are responsible for these differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Leaf samples (7±20 mg) were separated into ten phytochemical fractions representing growth and metabolism (lipids plus pigments, amino acids, organic acids, protein, residue), storage and transport (starch and sugars), and carbon-based defenses (phenolic glycosides, methanol:water-soluble tannins/phenolics and acetone-soluble tannins/phenolics) using a modi®ed sequential extraction method (Dickson 1979;Lindroth et al 1986; Mauette and Oechel 1987; Fig. 1).…”
Section: Sequential Separation Of 14 C-labeled Metabolic Fractionsmentioning
confidence: 99%
“…Leaf samples (7±20 mg) were separated into ten phytochemical fractions representing growth and metabolism (lipids plus pigments, amino acids, organic acids, protein, residue), storage and transport (starch and sugars), and carbon-based defenses (phenolic glycosides, methanol:water-soluble tannins/phenolics and acetone-soluble tannins/phenolics) using a modi®ed sequential extraction method (Dickson 1979;Lindroth et al 1986; Mauette and Oechel 1987; Fig. 1).…”
Section: Sequential Separation Of 14 C-labeled Metabolic Fractionsmentioning
confidence: 99%
“…as well as insect growth and survival (e.g. Lincoln et al, 1982;Lindroth et al, 1986;Seiber et af., 1980). However, the impact of such chemical variation on insect feeding behaviour and preferences may depend on whether the insect is a generalist or a specialist feeder (Kraft & Denno, 1982;.…”
Section: Introductionmentioning
confidence: 99%
“…3). The ability of Papilio canadensis to consume Populus tremuloides appears to be primarily based on the ability to detoxify phenolic glycosides by high esterase activity (Lindroth et al 1986(Lindroth et al , 1988Scriber et al 1989). Studies using backcrosses between Papilio glaucus and Papilio canadensis have indicated that the ability to use Populus tremuloides acts in a dose-dependent manner, where hybrids have intermediate abilities to detoxify these compounds (Scriber et al 1989(Scriber et al , 1999, as is also seen in these natural hybrid populations.…”
Section: Discussionmentioning
confidence: 94%
“…tulipifera is known to have a wide variety of defensive compounds, particularly sesquiterpene lactones (Lindroth et al 1986;Scriber et al 1987;Barbosa et al 1990), which P. glaucus is capable of handling, but P. canadensis is not (Lindroth et al 1986). The ability of P. glaucus to feed on L. tulipifera appears to be at least partly due to its ability to excrete unaltered sesquiterpene lactones (Frankfater et al 2005).…”
Section: Discussionmentioning
confidence: 96%